Stick or Carrot? Asymmetric Responses to Vehicle Registration Taxes in Norway - Alice Ciccone; Emilia Soldani (Environmental and Resource Economics, 2021)
Vehicle registrations have been shown to strongly react to tax reforms aimed at reducing CO﻿2 emissions from passengers' cars, but are the effects equally strong for positive and negative tax changes? The literature on asymmetric reactions to price and tax changes has documented asymmetries for everyday goods but has not yet considered durables. We leverage multiple vehicle registration tax (VRT) reforms in Norway and estimate their impact on within car-model substitutions. We estimate stronger effects for cars receiving tax cuts and rebates than for those affected by tax increases. The corresponding estimated elasticity is -~1.99 for VRT decreases and 0.77 for increases. As consumers may also substitute across car models, our estimates represent a lower bound.
Keywords: 330; CO2﻿ emissions intensity; New vehicles; Vehicle registration tax; Elasticity; Asymmetric response; Norway